(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Working conditions in poultry factories are inextricably linked with the uniqueness of the construction of the enterprise building, the method of keeping poultry, the degree of mechanization of the main and auxiliary technologies used in their care, climate, geographical conditions, and the season. Industrial type poultry farms are characterized by a certain level of physical pressure on the organs of movement support and emotions.